Сказки народов Сибири, Средней Азии и Казахстана - Аникин Владимир Прокопьевич (1995)
Экземпляры: КХ (19980914) / Инвентарный номер: 1022466 / Цена: 8750.00 / Сис.шифр: 82.3(2) / Авт.знак: С 42 / ГРНТИ: 17.71.91 / ББК: 82.3(0)-442.06